Renewable Energy Solutions in Agricultural Systems: Enhancing Sustainability through Solar and Wind Energy for Farm Operations - Sulaiman, Sulaiman; Na, Li; Hui, Zhou (Journal of Multidisciplinary Sustainability Asean, 2026)
Background. Agricultural systems are increasingly challenged by rising energy costs, greenhouse gas emissions, and dependence on fossil fuels, which undermine environmental sustainability and economic resilience. Renewable energy technologies, particularly solar and wind energy, offer promising alternatives to support farm operations while reducing environmental impacts. Integrating renewable energy into agricultural systems has the potential to enhance sustainability, improve energy efficiency, and strengthen climate resilience in rural areas. Purpose. This study aims to examine the role of solar and wind energy solutions in enhancing the sustainability of agricultural systems. The research focuses on evaluating their effectiveness in supporting farm operations, reducing carbon emissions, and improving economic viability for farmers. Method. A mixed-methods approach was employed, combining quantitative analysis of energy production, cost efficiency, and emission reductions with qualitative case studies from farms adopting solar and wind energy technologies. Data were collected through field measurements, energy audits, farmer surveys, and policy document analysis Results. The findings indicate that farms utilizing solar and wind energy experienced significant reductions in energy costs and carbon emissions, alongside improved energy self-sufficiency. Renewable energy integration also enhanced operational stability, particularly in irrigation, storage, and processing activities. Conclusion. Renewable energy solutions, especially solar and wind power, represent effective strategies for enhancing sustainability in agricultural systems. Their integration supports environmentally responsible farming while contributing to long-term economic and energy resilience.